Regulation of Ca2+ transient by PP2A in normal and failing heart - Lei, Ming; Wang, Xin; Ke, Yunbo; Solaro, R. John (Frontiers in Physiology, 2015)
Abstract: Calcium transient in cardiomyocytes is regulated by multiple protein kinases and phosphatases. PP2A is a major protein phosphatase in the heart modulating Ca2+ handling through an array of ion channels, antiporters and pumps, etc. The assembly, localization/ translocation, and substrate specificity of PP2A are controlled by different post-translational mechanisms, which in turn are linked to the activities of upstream signaling molecules. Abnormal PP2A expression and activities are associated with defective response to β-adrenergic stimulation and are indication and causal factors in arrhythmia and heart failure.